Simultaneous Culture and Biomachining of Copper in MAC Medium: A Comparison between Acidithiobacillus ferrooxidans and Sulfobacillus thermosulfidooxidans - Diaz Tena, E. (2018)
Biomachining will not be considered as a full-scale manufacturing technology until a stable, controlled, and continuous metal removal rate (MRR) is achieved. In this research work, a novel strategy that could promote its industrial implementation, namely simultaneous bacterial growth and machining of copper contained in oxygen-free copper (OFC) workpieces, was investigated. This proposal has the major advantage of being a single-stage process, thereby reducing total operating times and becoming more economical in comparison with conventional biomachining (downtime due to bacterial growth would disappear). The study was carried out using mesophilic (Acidithiobacillus ferrooxidans) and thermophilic (Sulfobacillus thermosulfidooxidans) extremophile bacteria in order to prevent the progressive decrease in the amount of metal removed per unit time. A constant MRR of 43 mg h-1 was achieved with A. ferrooxidans in the simultaneous process. Despite the accomplishment of a constant MRR, this value is lower than the maximum MRR obtained in conventional biomachining (109 mg h-1), probably due to the inability of ferric ions to come into contact with the metallic surface. With regard to the culture period in MAC medium, S. thermosulfidooxidans showed a slower growth rate (0.11 h-1) and lower ferrous ion oxidation level (0.12 g Fe2+ L-1 h-1) than A. ferrooxidans (0.17 h-1 and 0.22 g Fe2+ L-1 h-1, respectively) under optimal pH (1.5) and Fe2+ concentration (6 g L-1) conditions.